PENGARUH KUALITAS PRODUK, HARGA, DAN LOKASI DALAM MEMBENTUK KEPUASAN KONSUMEN PADA ES CENDOL SHAFA DI SITUBONDO DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Aziza, Ummi; Arief, Mohammad Yahya; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Marketing is a process of business activities to introduce a consumer product to and customers. The purpose of this study is to examine and test the Influence of Product Quality, Price, and Location in shaping consumer satisfaction on Es Cendol Shafa in Situbondo with Purchasing Decisions as Intervening Variables. The population in this study were consumers of Es Cendol Shafa in Situbondo. The sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using Smart PLS 3.0, showed that Product Quality has a significant effect on Purchasing Decisions; Location has a significant positive effect on Purchasing Decisions; Product quality has a significant positive effect on Consumer Satisfaction; Price has a significant positive effect on Consumer Satisfaction; Location has a significant positive effect on Consumer Satisfaction: Product quality has a significant negative effect on Consumer Satisfaction through Purchasing Decisions; Price has a significant negative effecton Consumer Satisfaction through Purchasing Decisions; Location has a significant negative effect on Consumer Satisfaction through Purchasing Decisions.